PENGARUH PERSEPSI MANFAAT PERSEPSI KEMUDAHAN PENGGUNAAN DAN ONLINE CUSTOMER REVIEW TERHADAP MINAT PENGGUNAAN APLIKASI MYPERTAMINA DI KABUPATEN GIANYAR - Pitria Dewi, Ni Komang; Sumerta, I Komang (Jurnal MBE Manajemen Bisnis, Equilibrium, 2024)
MyPertamina is a digital financial application that can be used to pay cashless fuel oil. This study was conducted to test whether the variables in this study had a joint and individual influence on the interest in using MyPertamina in Gianyar Regency. The number of target groups consisted of 96 respondents, with a stratified sampling technique and based on criteria. Data analysis used classical hypothesis testing and multiple linear regression analysis. Overall the results of the study show a positive and significant trend. The variables Perceived Usefulness (X1) and Online Customer Review (X3) partially have a unidirectional and real influence, however, perceived ease of use (X2) shows a positive but not significant trend, meaning that the more positive values generated, the greater the interest in MyPertamina, but the convenience provided by MyPertamina is not strong enough to affect interest in using MyPertamina actually.